A World of Blame to Go Around: Cross-Cultural Determinants of Responsibility and Punishment Judgments. (April 2019) - Feinberg, Matthew; Fang, Ray; Liu, Shi; Peng, Kaiping
Research finds collectivists make external attributions for others' behavior, whereas individualists make internal attributions. By focusing on external causes, collectivists should be less punitive toward those who harm others. Yet, many collectivistic cultures are known for strict retributive justice systems. How can collectivists simultaneously make external attributions and punish so harshly? We hypothesized that unlike individualists whose analytic tendencies engender a focus on mental states where judgments of accountability stem from perceptions of a harm-doer's agency, collectivists' holistic cognitive tendencies engender a focus on social harmony where judgments of accountability stem from perceived social consequences of the harmful act. Thus, what leads collectivists to make external attributions for behavior also leads to harsh punishment of those harming the collective welfare. Four cross-cultural studies found evidence that perceptions of a target's agency more strongly predicted responsibility and punishment judgments for individualists, whereas perceived severity of the harm was stronger for collectivists.